PENGEMBANGAN FISIK MOTORIK ANAK USIA DINI MELALUI PENDIDIKAN JASMANI KEGIATAN MELOMPAT TALI PADA TK SYAICHONA KHOLIL BALIKPAPAN - Suherman (Yayasan Pendidikan Islam dan Multikultural, 2021)
Abstract: Gross motor development as a process of developing physical movement through regular activity in the muscle and nerve centers. The research was carried out with the aim of increasing gross motor development in early childhood through jumping rope activities at Syaichona Kholil Kindergarten Balikpapan. The research was conducted using Classroom Action Research. The research subjects were early childhood students. The objects in this study are children aged 4-5 years through the gross motor skills of specific students on balance and strength. Techniques in collecting data by observation. The research instrument was through observation sheets. The data analysis technique used descriptive qualitative and quantitative. Classroom action research was conducted in two cycles. The steps in doing rope jumping activities are starting with the children doing pre-warming activities, then the students are divided into two groups, then the children jump rope with a height of 20 cm. Students who have jumped rope will be given a reward in the form of a star sticker. The gross motor elements observed in the jumping rope activity in Cycle I and Cycle II were balance and strength. The results of the research conducted that various components of gross motor aspects can improve the use of jumping rope activities. An increase in gross motor skills can be seen in the action before obtaining 14.28% or 2 students from 14 students with good criteria, in Cycle I obtained 71% or 10 students from 14 students with good criteria and Cycle II obtained 93% or 13 students from 14 students with good criteria. Students are able to carry out jumping movements with such a strong repulsion that they are able to land effectively and efficiently.